Sporadic Creutzfeldt-Jakob Disease in a Woman Married Into a Gerstmann-Sträussler-Scheinker Family: An Investigation of Prions Transmission via Microchimerism. Issue 8 (7th June 2018) - Areškevičiūtė, Aušrinė; Melchior, Linea Cecilie; Broholm, Helle; Krarup, Lars-Henrik; Granhøj Lindquist, Suzanne; Johansen, Peter; McKenzie, Neil; Green, Alison; Nielsen, Jørgen Erik; Laursen, Henning; Løbner Lund, Eva
Abstract: This is the first report of presumed sporadic Creutzfeldt-Jakob disease (sCJD) and Gerstmann-Sträussler-Scheinker disease (GSS) with the prion protein gene c.305C>T mutation (p.P102L) occurring in one family. The father and son were affected with GSS and the mother had a rapidly progressive form of CJD. Diagnosis of genetic, variant, and iatrogenic CJD was ruled out based on the mother's clinical history, genetic tests, and biochemical investigations, all of which supported the diagnosis of sCJD. However, given the low incidence of sCJD and GSS, their co-occurrence in one family is extraordinary and challenging. Thus, a hypothesis for the transmission of infectious prion proteins (PrP Sc ) via microchimerism was proposed and investigated. DNA from 15 different brain regions and plasma samples of the CJD patient was subjected to PCR and shallow sequencing for detection of a male sex-determining chromosome Y ( chr. Y ). However, no trace of chr. Y was found. A long CJD incubation period or presumed small concentrations of chr. Y may explain the obtained results. Further studies of CJD and GSS animal models with controlled genetic and proteomic features are needed to determine whether maternal CJD triggered via microchimerism by a GSS fetus might present a new PrP Sc transmission route.